Low levels of cardiovascular risk factors and coronary heart disease in a UK Chinese population. Issue 6 (December 1997) - Harland, J O; Unwin, N; Bhopal, R S; White, M; Watson, B; Laker, M; Alberti, K G
Abstract : OBJECTIVE: To compare the prevalence of cardiovascular risk factors and coronary heart disease in Chinese and Europid adults. DESIGN: Population based, cross sectional survey. SETTING: Newcastle upon Tyne, UK, 1991-93. SUBJECTS: Altogether 380 Chinese and 625 Europid adults, aged 25-64 years. MAIN OUTCOME MEASURES: Fasting lipid levels, blood pressure, body mass index (BMI), the proportions who smoked, and the prevalence of coronary heart disease based on the Rose angina questionnaire and major electrocardiographic abnormalities on resting 12 lead electrocardiogram (Minnesota codes 1.1-1.2). All figures were age adjusted to the 1991 England and Wales population. RESULTS: Altogether 183 and 197 Chinese, and 310 and 315 Europid men and women respectively were seen. Compared with Europid men, Chinese men had a lower mean total cholesterol concentration (5.1 versus 5.6 mmol/l, p < 0.001) and LDL cholesterol (3.2 versus 3.6 mmol/l, p < 0.001); lower BMI values (23.8 versus 26.1 kg/m-2, p < 0.001); and smoked less (23% versus 35%, p < 0.01)). Compared with Europid women, Chinese women also had lower mean lipid levels (total cholesterol: 4.9 versus 5.4 mmol/l p < 0.001, LDL cholesterol: 2.8 versus 3.1 mmol/l p < 0.001); BMI values (23.5 versus 26.1 kg/m-2, p < 0.001); and far fewer were smokers (1.4% versus 33%, p < 0.001). Chinese women, however, had higher mean systolic (121 versus 117 mmHg, p > 0.05) and diastolic (75 versus 68 mmHg, p < 0.001) blood pressures. The prevalence of coronary heart disease was significantly lower in Chinese than Europid men (4.9% versus 16.6%, p < 0.001) but not significantly different in women (7.3% versus 11.1%, p = 0.16). CONCLUSION: Strategies for UK Chinese are needed to maintain this favourable risk factor profile and prevent any potential increase in the risk of coronary heart disease associated with increasing acculturation.